To the Problem of Context - Kovalchuk (Babula), Liudmyla V. (Волинський державний університет імені Лесі Українки, 2007)
The article deals with the analysis of existing points of view on the notion of context. In this work we characterize context at micro- and macrolevels, we outline its typological characteristics. In the focus of our research, like of the contemporary communicative linguistics, is, first of all, the context which is equated with global conditions of communication which include sociocultural, cognitive, ethnopsychological and other parametres.
Keywords: context; context typology; micro- and macrolevel; explicit and implicit context; inner and outer context; communicative situation